Free access to medicines for the treatment of chronic diseases in Brazil - Noemia Urruth Leão Tavares; Vera Lucia Luiza; Maria Auxiliadora Oliveira; Karen Sarmento Costa; Sotero Serrate Mengue; Paulo Sergio Dourado Arrais; Luiz Roberto Ramos; Mareni Rocha Farias; Tatiane da Silva Dal Pizzol; Andréa Dâmaso Bertoldi
ABSTRACT OBJECTIVE To analyze the free access to medicines for the treatment of chronic diseases in the Brazilian population, according to demographic and socioeconomic factors. We also analyzed the most used pharmacological groups, according to funding source: free-of-charge or out-of-pocket paid. METHODS Analysis of data from the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos (PNAUM - National Survey on Access, Use and Promotion of Rational Use of Medicines), a population-based household survey, of cross-sectional design, based on probabilistic sample of the Brazilian population. We analyzed as outcome the prevalence of free access (free-of-charge) to all medicines for treatment of the reported chronic diseases, in the last 30 days. We studied the following independent variables: sex, age group, education in complete years of school, economic class, health plan, and geographical region of residence. We estimated the prevalences and 95% confidence intervals (95%CI) and applied the Pearson's Chi-squared test to assess the differences between the groups, considering a 5% significance level. RESULTS About half of adults and older adults who have had full access to the treatment of chronic diseases in Brazil obtained all needed medicines for free (47.5%; 95%CI 45.1-50.0). The prevalences of free access were higher among men (51.4%; 95%CI 48.1-54.8), age group of 40-59 years (51.1%; 95%CI 48.1-54.2), and in the poorest social classes (53.9%; 95%CI 50.2-57.7). The majority of medicines that act on the cardiovascular system, such as diuretics (C03) (78.0%; 95%CI 75.2-80.5), beta-blockers (C07) (62.7%; 95%CI 59.4-65.8), and the agents that work in the renin-angiotensin system (C09) (73.4%; 95%CI 70.8-75.8), were obtained for free. Medicines that act on the respiratory system, such as agents against obstructive airway diseases (R03) (60.0%; 95%CI 52.7-66.9) were mostly paid with own resources. CONCLUSIONS Free access to medicines for treatment of chronic diseases occurs to a considerable portion of the Brazilian population, especially for the poorest ones, indicating decreased socioeconomic inequalities, but with differences between regions and between some classes of medicines.